2014
DOI: 10.1097/tp.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Therapy in the Management of 63,593 Brain-Dead Organ Donors

Abstract: T3/T4 therapy results in more transplantable organs, with no detriment to posttransplantation graft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 15 publications
0
71
1
8
Order By: Relevance
“…Using the recommended protocol in cardiac donors as well as treating the recipients with T3 has shown improved outcome in one study (31), and use of T3 or T4 in potential donors showed increase in the number of organs successfully transplanted, with no detrimental effect on graft survival in a large retrospective cohort study of 63,593 donors over 10 years (82). However, several randomized clinical trials failed to substantiate these findings (31).…”
Section: Brain-dead Potential Organ Donorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Using the recommended protocol in cardiac donors as well as treating the recipients with T3 has shown improved outcome in one study (31), and use of T3 or T4 in potential donors showed increase in the number of organs successfully transplanted, with no detrimental effect on graft survival in a large retrospective cohort study of 63,593 donors over 10 years (82). However, several randomized clinical trials failed to substantiate these findings (31).…”
Section: Brain-dead Potential Organ Donorsmentioning
confidence: 94%
“…Increased mortality associated with low T3 levels is also correlated with increased cardiac risk factors, such as coronary calcification scores and arterial stiffness (72), lower left ventricular ejection fracture and higher mass index (63). Low free T3 and high rT3 levels have also been associated with increased risk for mortality in patients in the intensive care unit (ICU) (89,105), hospitalized cardiac patients (82), patients with congestive heart failure (CHF) (40,92) and patients with liver cirrhosis (34). Others have reported that the presence of nonthyroidal illness portends worsened overall prognosis in patients with enterocutaneous fistulas (49) and in burn patients (42).…”
Section: Treatment Of the Euthyroid Sick Syndromementioning
confidence: 98%
“…T 3 /T 4 therapy was originally introduced to improve the hemodynamic status of potential heart donors, and, although there is increasing evidence of its association with increased procurement of several other organs, 15 arguably it has its greatest impact on procurement of the heart.…”
Section: Perspectivementioning
confidence: 99%
“…À ce jour, à l'inverse des recommandations nord-américaines [14,15], une supplémentation hormonale thyroïdienne n'est pas retenue dans les recommandations françaises. Récemment, Novitzky et al ont analysé l'effet de l'administration d'hormones thyroïdiennes chez 65 000 DDME [56]. Les auteurs observaient avec une analyse multivariée que l'administration de ce traitement permettait de prélever davantage d'organes.…”
Section: Supplémentation Hormonaleunclassified